Maternal experience of intermittent kangaroo mother care for late preterm infants: a mixed-methods study in four postnatal wards in China - Zhang, B; Yue, J; Duan, Z; Zhao, Y; Williams, S; Huang, L; Zhang, X; Wu, W; Zhang, L; Liu, J; Zhao, G (BMJ Publishing Group, 2021)
Objective To describe how mothers of late preterm infants experienced the provision of intermittent kangaroo mother care (KMC) in four postnatal wards in different hospitals in China, under a pilot KMC project.